2021
DOI: 10.7759/cureus.14534
|View full text |Cite
|
Sign up to set email alerts
|

Aggressive Presentation of Streptococcus constellatus

Abstract: The Streptococcus anginosus group (SAG) consists of three bacteria (Streptococcus intermedius, Streptococcus constellatus, and Streptococcus anginosus) that are known commensals of the upper respiratory, digestive, and reproductive tracts. While a rare occurrence, these bacteria have the capability of causing devastating pyogenic infections and ensuing abscess formations. It is often difficult to distinguish this group as a contaminant or the offending organism (as it is often cultured in respiratory specimens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 9 publications
0
8
0
Order By: Relevance
“…Other retrospective studies describing the bacteriology and clinical features of empyema thoracis and lung abscess showed that among the 76 isolated strains of viridans streptococci, the most common were S. constellatus (21 strains), S. intermedius (17), and Streptococcus sanguis (10) ( Jerng et al, 1997 ). Moreover, there is an increase in the number of case reports that indicate S. constellatus as a pulmonary pathogen ( Morinaga et al, 2013 ; Elhussein and Hutchison, 2014 ; Price et al, 2015 ; Zhang et al, 2020 ; Vulisha et al, 2021 ). Taken together, the role of SAG in the pathogenesis of lung diseases is indisputable, with the leading role of S. constellatus and S. intermedius .…”
Section: Streptococcus Anginosus Group – Opportunistic Patho...mentioning
confidence: 99%
“…Other retrospective studies describing the bacteriology and clinical features of empyema thoracis and lung abscess showed that among the 76 isolated strains of viridans streptococci, the most common were S. constellatus (21 strains), S. intermedius (17), and Streptococcus sanguis (10) ( Jerng et al, 1997 ). Moreover, there is an increase in the number of case reports that indicate S. constellatus as a pulmonary pathogen ( Morinaga et al, 2013 ; Elhussein and Hutchison, 2014 ; Price et al, 2015 ; Zhang et al, 2020 ; Vulisha et al, 2021 ). Taken together, the role of SAG in the pathogenesis of lung diseases is indisputable, with the leading role of S. constellatus and S. intermedius .…”
Section: Streptococcus Anginosus Group – Opportunistic Patho...mentioning
confidence: 99%
“…Streptococcus constellatus is a subgroup of viridans streptococci widely distributed in the oral cavity, nasopharynx, gastrointestinal tract, and vagina ( 20 ). These bacteria have the capability of causing pyogenic infections and abscess formations mainly in the respiratory tract, brain, liver, bone, and soft tissues on a rare occurrence ( 21 ). So, how did this patient's abscess of the psoas major muscle arise?…”
Section: Discussionmentioning
confidence: 99%
“…14 patients in the literature with empyema with S. constellatus cultured from pleural fluid was enrolled. [12][13][14][15][16][17][18][19][20][21][22][23] The clinical information was shown in the table (Supplementary Table 3). 92.9% of patients were male.…”
Section: Literature Reviewmentioning
confidence: 99%